Diagnostic Accuracy of Computed Tomography in Active Pulmonary Tuberculosis - Qurat ul Ain; Ahmed, Adnan; Dahri, Mohsin Qasim; Dahri, Mohsin Qasim; Mirani, Kainat; Qurat-ul-Ain (Indus Journal of Bioscience Research, 2025)
Background: Diagnosing active pulmonary tuberculosis (PTB) remains difficult, particularly when sputum tests are inconclusive or delayed. This study examined how accurately computed tomography (CT) detects active PTB compared to sputum culture, the current reference standard. Methods: We enrolled 151 patients with suspected PTB who underwent both chest CT and sputum culture. Radiologists assessed CT scans for features suggestive of active disease. We compared CT findings to culture results and calculated sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall diagnostic accuracy. Results: CT identified active PTB in 96 patients, while sputum culture confirmed disease in 92. CT correctly classified 86 true positives and 49 true negatives. The test achieved a sensitivity of 89.5%, specificity of 89.0%, PPV of 93.4%, NPV of 83.0%, and overall accuracy of 89.4%. Conclusion: CT identified active pulmonary tuberculosis with high accuracy and performed well in both smear-positive and smear-negative cases. It serves as a reliable adjunct when bacteriological confirmation is unavailable or delayed, and may improve early diagnosis in high-burden settings.